(untitled) (Shanti Journal, 2022)
Several factors build mental agony for the Indian expatriate workers at Muscat in Oman. The researcher collected data from 120 respondents. All the respondents are working in various companies with their diverse designations. The researcher framed informal questionaries’ and asked them to the 120 respondents on various dates from 17/07/2021 to 27/01/2022. All the respondents are male employees aged about 22 to 55 years having Graduations in Engineering, Diploma in Engineering and Technical Training Certificates, Degree in graduations. The researcher collected the data meeting the respondents informally / incidentally at various premises in Muscat, Oman. The seven hypotheses are framed. The researcher finds that all the 07 factors do not give the mental agony equally to the respondents. The quality of the food, Family member response and Colleagues attitude give more mental agony to Indian expatriate rather than other factors. Hence, the employer must deputize a committee/ employee welfare officer to solve the mental agony.